Black Wave : Saudi Arabia, Iran and the Rivalry that Unravelled the Middle East - Ghattas, Kim (London Headline Publishing Group, 2020)
A timely and unprecedented examination of how the modern Middle East unravelled, and why it started with the pivotal year of 1979.
Include Index
Keywords: Radicalism -- Middle East -- Politics and government